Neoadjuvant chemotherapy versus debulking surgery in advanced tubo-ovarian cancers: pooled analysis of individual patient data from the EORTC 55971 and CHORUS trials. Issue 12 (December 2018) - Vergote, Ignace; Coens, Corneel; Nankivell, Matthew; Kristensen, Gunnar B; Parmar, Mahesh K B; Ehlen, Tom; Jayson, Gordon C; Johnson, Nick; Swart, Ann Marie; Verheijen, René; McCluggage, W Glenn; Perren, Tim; et al.
Summary: Background: Individual patient data from two randomised trials comparing neoadjuvant chemotherapy with upfront debulking surgery in advanced tubo-ovarian cancer were analysed to examine long-term outcomes for patients and to identify any preferable therapeutic approaches for subgroup populations. Methods: We did a per-protocol pooled analysis of individual patient data from the European Organisation for Research and Treatment of Cancer (EORTC) 55971 trial (NCT00003636 ) and the Medical Research Council Chemotherapy Or Upfront Surgery (CHORUS) trial (ISRCTN74802813). In the EORTC trial, eligible women had biopsy-proven International Federation of Gynecology and Obstetrics (FIGO) stage IIIC or IV invasive epithelial tubo-ovarian carcinoma. In the CHORUS trial, inclusion criteria were similar to those of the EORTC trial, and women with apparent FIGO stage IIIA and IIIB disease were also eligible. The main aim of the pooled analysis was to show non-inferiority in overall survival with neoadjuvant chemotherapy compared with upfront debulking surgery, using the reverse Kaplan-Meier method. Tests for heterogeneity were based on Cochran's Q heterogeneity statistic. Findings: Data for 1220 women were included in the pooled analysis, 670 from the EORTC trial and 550 from the CHORUS trial. 612 women were randomly allocated to receive upfront debulking surgery and 608 to receive neoadjuvant chemotherapy. Median follow-up was 7·6 years (IQR 6·0–9·6; EORTC, 9·2 years [IQR 7·3–10·4]; CHORUS, 5·9 years [IQR 4·3–7·4]). Median age was 63 years (IQR 56–71) and median size of the largest metastatic tumour at diagnosis was 8 cm (IQR 4·8–13·0). 55 (5%) women had FIGO stage II–IIIB disease, 831 (68%) had stage IIIC disease, and 230 (19%) had stage IV disease, with staging data missing for 104 (9%) women. In the entire population, no difference in median overall survival was noted between patients who underwent neoadjuvant chemotherapy and upfront debulking surgery (27·6 months [IQR 14·1–51·3] and 26·9 months [12·7–50·1], respectively; hazard ratio [HR] 0·97, 95% CI 0·86–1·09; p=0·586). Median overall survival for EORTC and CHORUS patients was significantly different at 30·2 months (IQR 15·7–53·7) and 23·6 months (10·5–46·9), respectively (HR 1·20, 95% CI 1·06–1·36; p=0·004), but was not heterogeneous (Cochran's Q, p=0·17). Women with stage IV disease had significantly better outcomes with neoadjuvant chemotherapy compared with upfront debulking surgery (median overall survival 24·3 months [IQR 14·1–47·6] and 21·2 months [10·0–36·4], respectively; HR 0·76, 95% CI 0·58–1·00; p=0·048; median progression-free survival 10·6 months [7·9–15·0] and 9·7 months [5·2–13·2], respectively; HR 0·77, 95% CI 0·59–1·00; p=0·049). Interpretation: Long-term follow-up data substantiate previous results showing that neoadjuvant chemotherapy and upfront debulking surgery result in similar overall survival in advanced tubo-ovarian cancer, with better survival in women with stage IV disease with neoadjuvant chemotherapy. This pooled analysis, with long-term follow-up, shows that neoadjuvant chemotherapy is a valuable treatment option for patients with stage IIIC–IV tubo-ovarian cancer, particularly in patients with a high tumour burden at presentation or poor performance status. Funding: National Cancer Institute and Vlaamse Liga tegen kanker (Flemish League against Cancer).